Increasing the corrosion resistance of ferrosilide in hot sulfuric acid by alloying with chromium, nickel and molybdenum - Siharov, Ye. M.; Smirnov , O. M.; Pokhvalityi , A. A.; Orlov , D. V.; Skorobahatko , Yu. P. (Theory and Practice of Metallurgy, 2026)
The corrosion resistance of ferrosilides of the Fe-Si-Cr-Ni-Mo-Mn system in concentrated sulfuric acid in the temperature range of 25-200°C was investigated. The corrosion rate was calculated based on electrochemical parameters using passivation and temperature dependence models of the Arrhenius type. It was confirmed that the main factor determining corrosion resistance is the silicon content. The existence of a critical Si content threshold was shown, upon reaching which a continuous passive SiO₂ film is formed, which provides a reduction in the corrosion rate by 1-2 orders of magnitude. Characteristic temperature ranges of the corrosion process were identified: stable passivation (25-80°C), transitional regime (80-150°C) and degradation of the passive state (150-200°C). It has been shown that Cr and Mo in Fe-Si alloys enhance the stability of the passivated state, particularly at high sulfuric acid temperatures, whereas Ni primarily affects the electrochemical characteristics, and Mn reduces the effectiveness of passivation. The effectiveness of adding chromium to Fe-Si alloys increases proportionally with the Si content; molybdenum stabilizes passivation at acid temperatures above 150°C and reduces the rate of localized corrosion; nickel is not a determining factor at high acid temperatures. The influence of operational factors (turbulence, erosion, impurities) on the corrosion rate has been determined. The expected corrosion rates for the studied alloys in sulfuric acid have been calculated, taking into account industrial operating conditions. The experimental data obtained can be used to develop new corrosion-resistant materials and optimize the composition of Fe-Si alloys for operation in high-temperature aggressive environments of concentrated sulfuric acid.